Cloning and Characterization of Two Putative P-Type ATPases from the Marine Microalga Dunaliella maritima Similar to Plant H+-ATPases and Their Gene Expression Analysis under Conditions of Hyperosmotic Salt Shock - Dmitrii A. Matalin; Dmitrii E. Khramov; Alexey V. Shuvalov; Vadim S. Volkov; Yurii V. Balnokin; Larissa G. Popova (Plants, 2021)
The green microalga genus Dunaliella is mostly comprised of species that exhibit a wide range of salinity tolerance, including inhabitants of hyperhaline reservoirs. Na+ content in Dunaliella cells inhabiting saline environments is maintained at a fairly low level, comparable to that in the cells of freshwater organisms. However, despite a long history of studying the physiological and molecular mechanisms that ensure the ability of halotolerant Dunaliella species to survive at high concentrations of NaCl, the question of how Dunaliella cells remove excess Na+ ions entering from the environment is still debatable. For thermodynamic reasons it should be a primary active mechanism; for example, via a Na+-transporting ATPase, but the molecular identification of Na+-transporting mechanism in Dunaliella has not yet been carried out. Formerly, in the euryhaline alga D. maritima, we functionally identified Na+-transporting P-type ATPase in experiments with plasma membrane (PM) vesicles which were isolated from this alga. Here we describe the cloning of two putative P-type ATPases from D. maritima, DmHA1 and DmHA2. Phylogenetic analysis showed that both ATPases belong to the clade of proton P-type ATPases, but the similarity between DmHA1 and DmHA2 is not high. The expression of DmHA1 and DmHA2 in D. maritima cells under hyperosmotic salt shock was studied by qRT-PCR. Expression of DmHA1 gene decreases and remains at a relatively low level during the response of D. maritima cells to hyperosmotic salt shock. In contrast, expression of DmHA2 increases under hyperosmotic salt shock. This indicates that DmHA2 is important for overcoming hyperosmotic salt stress by the algal cells and as an ATPase it is likely directly involved in transport of Na+ ions. We assume that it is the DmHA2 ATPase that represents the Na+-transporting ATPase.